Clinical Outcomes of Second- versus First-Generation Carotid Stents: A Systematic Review and Meta-Analysis - Mazurek, Adam; Malinowski, Krzysztof; Rosenfield, Kenneth; Capoccia, Laura; Speziale, Francesco; de Donato, Gianmarco; Setacci, Carlo; Wissgott, Christian; Sirignano, Pasqualino; Tekieli, Lukasz; Karpenko, Andrey; Kuczmik, Waclaw; et al. (Journal of clinical medicine, 2022)
Background: Single-cohort studies suggest that second-generation stents (SGS; “mesh stents”) may improve carotid artery stenting (CAS) outcomes by limiting peri- and postprocedural cerebral embolism. SGS differ in the stent frame construction, mesh material, and design, as well as in mesh-to-frame position (inside/outside). Objectives: To compare clinical outcomes of SGS in relation to first-generation stents (FGSs; single-layer) in CAS. Methods: We performed a systematic review and meta-analysis of clinical studies with FGSs and SGS (PRISMA methodology, 3302 records). Endpoints were 30-day death, stroke, myocardial infarction (DSM), and 12-month ipsilateral stroke (IS) and restenosis (ISR). A random-effect model was applied. Results: Data of 68,422 patients from 112 eligible studies (68.2% men, 44.9% symptomatic) were meta-analyzed. Thirty-day DSM was 1.30% vs. 4.11% (p < 0.01, data for SGS vs. FGS). Among SGS, both Casper/Roadsaver and CGuard reduced 30-day DSM (by 2.78 and 3.03 absolute percent, p = 0.02 and p < 0.001), whereas the Gore stent was neutral. SGSs significantly improved outcomes compared with closed-cell FGS (30-day stroke 0.6% vs. 2.32%, p = 0.014; DSM 1.3% vs. 3.15%, p < 0.01). At 12 months, in relation to FGS, Casper/Roadsaver reduced IS (−3.25%, p < 0.05) but increased ISR (+3.19%, p = 0.04), CGuard showed a reduction in both IS and ISR (−3.13%, −3.63%; p = 0.01, p < 0.01), whereas the Gore stent was neutral. Conclusions: Pooled SGS use was associated with improved short- and long-term clinical results of CAS. Individual SGS types, however, differed significantly in their outcomes, indicating a lack of a “mesh stent” class effect. Findings from this meta-analysis may provide clinically relevant information in anticipation of large-scale randomized trials.